PTH-020 Outcomes of endoscopic stenting for malignant duodenal obstruction – experience of a single centre service. (June 2019) - Odedra, Priyan; Amin, Vishal; Goodchild, George; Martin, Harry; Johnson, Gavin; Pereira, Stephen; Webster, George; Chapman, Michael
Abstract : Introduction: Duodenal obstruction may occur as a complication of duodenal, locally advanced or metastatic cancer. The resulting gastric outlet obstruction may reduce quality of life and life expectancy and the physiological mileu of malnutrition may interrupt palliative chemotherapy. We aim to evaluate of the technical and clinical outcomes of patients undergoing duodenal stent placement for malignant duodenal obstruction. Methods: Retrospective study of all patients referred for endoscopic duodenal stent placement from Jan 2014 - Jan 2018. Data was collected from endoscopy procedure records and electronic patient records. All patients with intent for duodenal stenting were included. Technical success was defined by endoscopic or radiographic evidence of satisfactory stent position. Outcome measures included removal of enteral tube (NG/NJ), cessation of vomiting, recommencement of oral nutrition, initiation or resumption of chemotherapy, complications and overall survival. Results: 50 patients were referred for duodenal stenting (F=31, median age 68 years). CT scans were available for all patients and all cases were reviewed within our specialist MDM. The level of the obstruction was D1 (26/50), D2 (17/50) and D3 (7/50). Aetiology of malignant obstruction was: pancreatic (n=15), gastric (n=7), ovarian (n=6), cholangiocarcinoma (n=5), duodenal (n=5), colorectal (n=3), breast (n=2) and hepatocellular (n=1). Stenting was attempted in 48 patients (2 were deemed unfit). Successful stent placement was achieved in 43/48 (90%) of patients, with a failure to stent the remaining 5 patients due to an inability to cross the stricture with a wire. A total of 51 uncovered, self-expanding 22 mm diameter metal stents were placed in 43 patients (1 patient required 2 stents at the index procedure, 6 patients required 1 further stent and 1 patient required 2 further stents, ). The median stent length was 9 cm (range 6–12 cm). Technical success rates were 90%. Clinical success rates were as follows: Subsequent removal of enteral tube post-procedure 68%, cessation of vomiting 64%, recommencement of oral diet 58%, further chemotherapy 29%. Overall 28 day survival was 85% and 6 month survival was 33% (median survival 66 days). There were no immediate complications following stent placement. 1 patient developed biliary sepsis 5 days post-stenting (previously normal LFTs) and died within 28 days. 3 patients developed obstructive jaundice following stenting (at 4 months, 8 months and 21 months), which was successfully treated with percutaneous stenting in all cases. Conclusion: Providing a guidewire can be passed across the stricture, duodenal stenting for malignancy has a high technical success rate in our centre. Early clinical benefit is seen in the majority of patients, and of the 41 patients alive at 3 months, only 3 (7%) required re-intervention during this period. At 6 months, 16 patients were alive, 7 of whom (44%) had required re-intervention. This single centre experience demonstrates high technical and clinical success rates for stenting in patients with malignant duodenal obstruction, with benefit maintained well beyond 3 months. In those patients that survived >6 months, half had further chemotherapy.